Membudayakan Magrib Mengaji di Desa Tamiang - Amru Hasibuan; Akhir Saleh Pulungan; Ismail Nasution; Kali Junjung Hasibuan; Fitri Yani Nasution; Dina Kumala Sari; Nuratizah Siregar; Nursamunah Pasaribu; Milda Sartika Hasibuan (Yayasan Perguruan Kampus, 2025)
The habit of reading the Qur'an at Maghrib prayer is one of the efforts to shape a young generation with noble morals and strong religious knowledge. However, in the region, this tradition is starting to diminish due to technological developments, lack of parental attention and minimal religious activities for children. Community service activities with the theme